Sustainable Agricultural Engineering Technologies and Applications - Sultan, Muhammad; Zhou, Yuguang; Den, Walter; Sajjad, Uzair (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a continuation of our previous reprint "Sustainable agricultural, biological, and environmental engineering applications" [ISBN 978-3-0365-2921-9], which was published in January 2022. The reprint contains research and review works focused on agricultural engineering technologies and applications. In this regard, the reprint covers topics including agricultural storage, quality evaluation of fruits, evaporative cooling and desiccant systems, solar coffee roasting, solar yogurt processing, greenhouse environment, greenhouse ventilation, greenhouse thermal requirements, aquaculture production system, bioreactor landfill, waste management, fertilization reduction in agriculture, sustainable porous surfaces, simulation and modeling, artificial intelligence, and machine learning. Such agricultural engineering studies are urgently needed in the 21st century, particularly from the perspective of the agriculture-energy-food security nexus.